Acute Cholestatic Hepatitis A Virus Infection Presenting with Hemolytic Anemia and Renal Failure: A Case Report - Robert T. Lapp; Fedja Rochling (Case Reports in Hepatology)
Hepatitis A virus is the most common acute viral hepatitis worldwide with approximately 1.5 million cases annually. Hepatitis A virus infection in general is self-limited. In rare cases, hepatitis A virus infection may cause renal failure, hemolytic anemia, and/or cholestasis. We report the first case of acute cholestatic hepatitis A virus infection complicated by hemolytic anemia, and renal failure in one patient. A 42-year-old Caucasian male presented with cholestasis, hemolytic anemia and renal failure after consuming street tacos in Central and South America while on a business trip. His protracted course required corticosteroid therapy, multiple sessions of plasma exchange, and numerous units of packed red blood cells. This case demonstrates the importance of vaccination in high-risk adults. A prompt diagnosis of acute hepatitis A virus infection is essential, as uncommon presentations may delay diagnosis leading to permanent morbidity and potentially death in fulminant cases. We also demonstrate the efficacy of treatment of cholestatic hepatitis A virus infection, hemolytic anemia, and renal failure with corticosteroids and plasma exchange.